A study of cycling intention among Universiti Utara Malaysia - Chew, Yi Shen; Gan, Loo Kwan; Lim, Kok Meng; Aziz, Zulkufli (2017)
Recently, the fast growing trend in the logistics industry causes the concern towards the green transportation arises from the society. Universiti Utara Malaysia (UUM), which having a 1061 hectares campus, would requires sufficient transportation for students to travel around the campus. The main mode of transportation provides by UUM management is buses.However, the shuttle bus services cannot fulfill the huge demand of students. So, many of the students prefer to drive their own private vehicles rather than using shuttle bus in campus. This would increase the carbon footprint and rate of accidents happened.In order to maintain the green environment, cycling behavior should be encourage for every students. Thus, this study aimed to determine factors that influence the student’s cycling intentions in campus by using Ajzen's Theory of Planned Behavior such as attitude, social environment, perception and infrastructure as a theoretical framework. Approximately 400 undergraduate students in UUM are chosen to complete the questionnaire provided by using convenience technique.The results of Cronbach’s alpha score for the independent variables (IV) and dependent variable (DV) is 0.944.There is significant relationship between IVs and DV among UUM students.